Can Exercise Make You Smarter, Happier, and Have More Neurons? A Hormetic Perspective - Gradari, Simona; Pallé, Anna; McGreevy, Kerry R.; Fontán-Lozano, Ángela; Trejo, José L. (Frontiers in Neuroscience, 2016)
Exercise can make you smarter, happier and have more neurons depending on the dose (intensity) of the training program. It is well recognized that exercise protocols induce both positive and negative effects depending on the intensity of the exercise, among other key factors, a process described as a hormetic-like biphasic dose-response. However, no evidences have been reported till very recently about the biphasic response of some of the potential mediators of the exercise-induced actions. This hypothesis & theory will focus on the adult hippocampal neurogenesis as a putative physical substrate for hormesis responses to exercise in the context of exercise-induced actions on cognition and mood, and on the molecular pathways which might potentially be mediating these actions.